Ultrahigh-performance vector magnetic field sensor with wedge-shaped fiber tip based on surface plasmon resonance and magnetic fluid - Hao Zijian; Li Yongxi; Pu Shengli; Wang Jia; Chen Fan; Lahoubi Mahieddine (Nanophotonics)
A novel fiber-optic vector magnetic field sensor and its sensing quality dependent of fabrication method has been proposed and investigated. The proposed sensor has two surfaces on the tip of a multimode fiber, which is used as the sensing probe. By plating different thickness of gold film on the surfaces, surface plasmon resonance (SPR) can be generated and the signal can be reflected by the surfaces as well. Meanwhile, magnetic fluid (MF) as the magnetic field sensitive material is packed around the sensing probe. The experimental results prove that the response of MF to external magnetic field can be used to sense magnetic field intensity and direction via monitoring the dip wavelength of SPR. The obtained refractive index (RI) sensitivities are 2105 nm/RIU (RI range: 1.332–1.365) and 6692 nm/RIU (RI range: 1.372–1.411), magnetic field intensity sensitivities are 11.67 nm/mT (0°), and −0.47 nm/mT (90°). Besides, the proposed sensing probe is ultracompact and the footprint is extremely small (the length of sensing part is only 615 μm), which is very helpful for magnetic field detection in narrow space and gradient field.